57 STENTING FOR SUPERIOR VENA CAVA OBSTRUCTION IN PEDIATRIC HEART TRANSPLANT RECIPIENTS. Issue 1 (1st January 2007) - Burns, S. A.; Seib, P. M.; Fontenot, E. E.; Frazier, E. A.; Sachdeva, R.
Abstract : Purpose: Superior vena cava (SVC) obstruction can be a complication of reconstructive surgery done at the time of heart transplantation. Pediatric patients are at a higher risk compared with adults due to their smaller size, growth potential, multiple central line access, and complex native venous anatomy related to congenital heart disease. SVC obstruction can not only make these patients symptomatic but also limit access for obtaining cardiac biopsy. We reviewed our experience with relief of SVC obstruction using endovascular stents in pediatric heart transplant recipients. Methods: A retrospective review of medical records of patients (< 18 years) who were followed at our institution after cardiac transplant was performed. The study cohort was formed by patients who required endovascular stent placement for relief of SVC obstruction. Data retrieved included underlying cardiac diagnosis, age and weight at transplant, surgical technique of transplant (cavocaval vs biatrial anastomosis), presenting symptoms, time since transplant when SVC stent was placed, any procedural complications, and need for reintervention. Results: From March 1990 to June 2006, 138 pediatric patients were followed at our institution after heart transplantation. Of these, 7 developed SVC obstruction and formed the study cohort. Median age at transplant was 9 months (2.5-180 months); median weight was 8.7 kg (3.4-76 kg); cardiac diagnosis was heterotaxy syndrome (3), atrioventricular canal defect (1), double-outlet right ventricle (1), tricuspid atresia (1), hypoplastic left heart syndrome (1). Surgical technique at transplant involved cavocaval anastomosis in six and biatrial anastomosis in one. One patient had a SVC stent placed at transplant surgery due to severe obstruction. One patient presented with persistent pleural effusions and facial swelling; others were asymptomatic and diagnosed by echocardiography and/or cardiac catheterization. Median time from transplant surgery to SVC stent placement was 2 months (0-14 months). During a median follow-up of 4 years since transplant, one required redilation of SVC stent and two required an additional SVC stent. There were no complications related to stent placement. Conclusion: SVC obstruction can be an important although uncommon complication, especially in infants undergoing heart transplant using cavocaval technique. This obstruction can be safely and effectively relieved using endovascular stents.